Stíny - Králová, Balbína (Vysoké učení technické v Brně. Fakulta výtvarných umění, 2024)
Výstupem mé diplomové práce je soubor maleb suchým pastelem na plátně. Skrze záměrnou deformaci postav, kterou využívám jako výtvarný výrazový prostředek, se snažím zachytit křehkou povahu lidské existence, charakterizovanou nestabilitou a pomíjivostí. Náměty vzniklých maleb jsou portréty, které zobrazují mé sestry a mě.

The result of my thesis is a set of paintings in dry pastel on canvas. Through the deliberate deformation of figures, which I use as a means of artistic expression, I try to capture the fragile nature of human existence, characterized by instability and transience. The subjects of the resulting paintings are portraits that depict my sisters and me.
Shades
Keywords: malba; portrét; suchý pastel; fotografie; záznam; nestálost; destrukce; sestry; painting; portrait; soft pastel; photography; record; volatility; destruction; sisters